Marketing Strategy Selection System Based on Purchasing Decisions at Company X - Andriana, Iyan; Henny , Henny; Gunawan, Reynaldi; Afiff, Fatimah Zahra (Proceeding of International Conference on Informatics, Engineering, Science & Technology, 2025)
The appropriate marketing strategy selection system in this case is the design of a decision support system to quickly and accurately identify which elements of the marketing mix should be maintained or improved based on consumer responses. The research method involved collecting data through questionnaires designed from marketing mix variables, namely product, promotion, process, price, distribution, and physical evidence. The questionnaire results were compiled and interpreted using multiple linear regression analysis. Each calculation and analysis result was then stored in a database, supported with interactive forms, and presented through visual reports in Microsoft Access. This design provides two categories of information: first, users obtain the percentage of simultaneous influence, namely the combined effect of the seven marketing mix variables along with the hypothesis testing results; second, users obtain information on the partial influence of each marketing mix variable on purchasing decisions, including their significance levels. The second type of information is presented by separating the significant group of variables from the non-significant ones. The final outcome of the system design is a ranked list of significant variables, from the largest to the smallest percentage, providing users with clear guidance on which variables should be maintained and which should be improved. Thus, this decision support system concept helps the management of Company X transform data into high-quality information that can serve as the basis for strategic decision-making.